Effect of FADS1 SNPs rs174546, rs174547 and rs174550 on blood fatty acid profiles and plasma free oxylipins - Rabehl, Miriam; Wei, Zeren; Leineweber, Can G.; Enssle, Jörg; Rothe, Michael; Jung, Adelheid; Schmöcker, Christoph; Elbelt, Ulf; Weylandt, Karsten H.; Pietzner, Anne (Frontiers in Nutrition, 2024)
Previous studies have indicated that activity of fatty acid desaturases (FADS), namely FADS1, is involved in cardiometabolic risk. Some previous studies indicated an increased risk of atherosclerosis with genotypes leading to higher levels of FADS1 activity, while other data indicate that genotypes with lower FADS1 expression, as well as experimental knock-down of FADS1 expression, increases metabolic risk such as obesity and associated metabolic dysfunction. Supporting this association between genotypes with decreased FADS1 activity, obesity and metabolic-dysfunction associated fatty liver disease (MAFLD), recent experimental data have shown that FADS1 knockdown can promote lipid accumulation and lipid droplet formation in liver cells. In the data presented here we analyzed differences in the FADS1 single-nucleotide polymorphism (SNPs) rs174546, rs174547, and rs174550 and their effect on blood fatty acids as well as free oxylipins in a cohort of 85 patients presenting to an academic metabolic medicine outpatient center. We found significantly lower blood levels of omega-6 polyunsaturated fatty acid (n-6 PUFA) arachidonic acid (AA), but no significant differences in n-3 PUFAs eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) in patients with the homozygous ancestral (minor) FADS1 genotype. There were no significant differences in liver fat as assessed by Fibroscan ultrasound measurements and no significant differences in arachidonic-acid derived lipid mediators such as thromboxane b2, with trends towards lower levels with the homozygous ancestral genotype. This tendency towards lower levels of lipid mediators was also found for a variety of other n-6 and n-3 PUFA derived oxylipins commonly associated with either inflammation promoting (n-6 PUFA derived mediators) or inflammation dampening (n-3 PUFA derived mediators).